RARE-23. PRIMARY INTRA-AXIAL CENTRAL NERVOUS SYSTEM INFLAMMATORY MYOFIBROBLASTIC TUMOR, ALK NEGATIVE: A RARE ENTITY. (5th November 2018) - Pflederer, Nicholas; Gross, John; Bridge, Julia; Nguyen, Cam; Ruma, Thomas
Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare spindle cell neoplasm with admixed inflammatory cells which occurs mainly in the abdomen or thoracic cavity of children or young adults. Primary CNS IMT is exceedingly rare with roughly 100 reported cases in the world literature, most of which are extra-axial and occur as a dural-based mass. Herein, we describe a rare case of intra-axial primary CNS IMT. A 24 year-old healthy female presented to the ER after falling and striking her head. A CT scan revealed an acute intraparenchymal hemorrhage, as well as a mass within the right frontoparietal lobe. Subsequent MRI was performed further characterizing the lesion as a 3.0 cm intra-axial tumor. Craniotomy was performed displaying a circumscribed neoplasm with relatively bland spindle cells arranged in fascicles with an admixed lymphoplasmacytic infiltrate. Mitotic activity was present but limited. Immunohistochemistry (IHC) was positive for TLE1 and vimentin but negative for GFAP, ALK, SMA, MUC4, KIT and β-catenin. Additional molecular testing by FISH for ALK (2p23) rearrangement was negative. We report a rare case of intra-axial primary CNS ALK Negative IMT. Approximately half of all IMTs harbor a clonal translocation that activates the anaplastic lymphoma kinase (ALK)-receptor tyrosine kinase at the 2p23 locus. As a result, ALK is overexpressed and can be detected by IHC or via molecular diagnostics (FISH, RNA sequencing or RT-PCR). Since this case was processed, additional novel anomalies involving rearrangements in ROS1, RET, ETV6 and/or NTRK3 genes have been described and could lead to promising therapeutic targets in the future.